Discrepancia entre SpO2 y SaO2 al diagnóstico de cuatro generaciones - Sandra Lucas; Inês Santos; Filipe Alfaiate; Diogo Dias; Ireneia Lino (Sociedade Galega de Medicina Interna, 2021)
Pulse oximetry measures the peripheral oxy-haemoglobin saturation (SpO2) which is a surrogate marker for arterial oxy-haemoglobin saturation (SaO2). SaO2 estimation is subjected to both oximeter proper functioning, patient characteristics and haemoglobin disturbances. A 82-year-old man goes to the emergency with cough, dyspnoea and fever. He has haemolytic anaemia. His kids also have anaemia. Examination showed fine crackles in pulmonary auscultation of the lower two thirds of the right lung and splenomegaly. SpO2 was 80% (FiO2 21%). Arterial blood gas analysis: pH 7.514; PaCO2 23.4 mmHg; PaO2 43.2 mmHg; Hb 13.0 g/dL. Chest X-ray suggesting an infectious process. He was admitted to the hospital with the diagnosis of pneumonia. During hospitalization we verify discrepancy between SpO2 and SaO2; haemolytic anaemia. The patient had a respiratory improvement and was discharged to external consult, dying months later. To clarify the discrepancy between SpO2 and SaO2 results; confirm the hereditary nature and identify the haemolytic anaemia. We did a retrospective familiar study based on the patient's clinical processes. Three children were identified with anaemia. Two of the children have known their anaemia for 35 years - studied in the context of respiratory infections with haemolytic crisis due to Lepore haemoglobinopathy and β-thalassemia, respectively. The patient previously diagnosed with Lepore haemoglobinopathy, currently undergoing hospital anaemia study, was diagnosed with Köln Hb. The discrepancy between SpO2 and SaO2 in association with a familiar haemolytic anaemia resulted in the diagnosis of autosomal dominant Köln haemoglobinopathy. The advances in the means of diagnosis enabled the probable diagnosis of 19 family members distributed over 4 generations.